SCRUTINIZING STUDENTS ONLINE LEARNING PERFORMANCE: A CASE STUDY ON STUDENT AGENCY - Mulyani, Martina; Novianti, Alviaderi (University of Kuningan, 2022)
This study aims to recognize the students’ mindset profile and find out how mindset as one of the elements of agency helps senior high school students to cope with difficulties in online learning. This study used a qualitative case study approach involving two students from different Senior High Schools in Cimahi. This study which specifically focused on the mindset of student agency gained its data from observation, interview, and documentation. The results of the analysis revealed that belief in one’s capability is the main element in mindset since it influences one’s attitude towards online learning, achievement in learning, and resilience concerning learning online. Regarding to the result of the study, it can be concluded that developing student agency can be started by encouraging students to believe in their capacity.